Original paperAsthma-chronic obstructive pulmonary disease overlap syndrome in Poland. Findings of an epidemiological study - Brzostek, Dorota; Kokot, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Recent years have seen an increased interest in asthma-chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS). Aim : In 2012, Takeda Polska conducted a non-interventional epidemiological study aimed at identifying the typical phenotype of ACOS patients receiving pulmonary care. Material and methods : The study enrolled a total of 12,103 of smoking patients above 45 years of age (mean age: 61.5 years; mean duration of smoking: 28.4 pack-years). A total of 68.6% of patients represented the frequent-exacerbation phenotype (mean number of exacerbations during 12 months: 2.11), and 56.4% of patients from the group comprising 12,103 participants were hospitalized at least once during their lifetime due to a respiratory system disease (mean number: 3.82 ±3.76). Results : The most commonly found asthma symptoms included paroxysmal dyspnoea with wheezing, and good response to inhaled steroids. The most frequently identified COPD-associated symptoms were: long-lasting reduction in forced expiratory volume in 1 s (FEV 1 ) (< 80% after administering a bronchodilator) and chronic productive cough. Eighty-five percent of patients were diagnosed with concomitant diseases, predominantly arterial hypertension (62.9%) and metabolic diseases (metabolic syndrome, obesity, type 2 diabetes – 46.4% in total). Conclusions : A clinically severe course of ACOS and the presence of concomitant diseases should be regarded as factors justifying an individual selection of inhalation therapy which specifically takes into account anti-inflammatory treatment and patient safety.